A Performance Study of Sequential IO on WindowsNT„¢ 4.0 - Gray, Jim; Riedel, Erik; van Ingen, Catharine (Advanced Computing Systems Association, 1997)
This paper investigates the most efficient way to read and write large sequential files using the Windows NT™ 4.0 File System. The study explores the performance of Intel Pentium Pro™ based memory and IO subsystems, including the processor bus, the PCI bus, the SCSI bus, the disk controllers, and the disk media. We provide details of the overhead costs at various levels of the system and examine a variety of the available tuning knobs. The report shows that NTFS out-of-the box read and write performance is quite good, but overheads for small requests can be quite high. The best performance is achieved by using large requests, bypassing the file system cache, spreading the data across many disks and controllers, and using deep-asynchronous requests.